Drug Leads from Endophytic Fungi: Lessons Learned via Scaled Production - Graf, Tyler N.; Kao, Diana; Rivera-Chávez, José; Gallagher, Jacklyn M.; Raja, Huzefa A.; Oberlies, Nicholas H. (Planta Medica, 2020)
Recently, the isolation and elucidation of a series of polyhydroxyanthraquinones were reported from an organic extract of a solid phase culture of an endophytic fungus, Penicillium restrictum (strain G85). One of these compounds, ω-hydroxyemodin (1), showed promising quorum-sensing inhibition against clinical isolates of methicillin-resistant Staphylococcus aureus (MRSA) in both in vitro and in vivo models. The initial supply of 1 was 19 mg, and this amount needed to be scaled by a factor of 30 to 50 times, in order to generate material for further in vivo studies. To do so, improvements were implemented to enhance both the fermentation of the fungal culture and the isolation of this compound, with the target of generating > 800 mg of study materials in a period of 13 wk. Valuable insights, both regarding chemistry and mycology, were gained during the targeted production of 1 on the laboratory-scale. In addition, methods were modified to make the process more environmentally friendly by judicious choice of solvents, implementing procedures for solvent recycling, and minimizing the use of halogenated solvents.
Keywords: Penicillium restrictum Aspergillaceae; polyhydroxyanthraquinone; ω-hydroxyemodin; Silybum marianum Asteraceae; fungal endophyte